2012
DOI: 10.1890/110136
|View full text |Cite
|
Sign up to set email alerts
|

When the river runs dry: human and ecological values of dry riverbeds

Abstract: Temporary rivers and streams that naturally cease to flow and dry up can be found on every continent. Many other water courses that were once perennial now also have temporary flow regimes due to the effects of water extraction for human use or as a result of changes in land use and climate. The dry beds of these temporary rivers are an integral part of river landscapes. We discuss their importance in human culture and their unique diversity of aquatic, amphibious, and terrestrial biota. We also describe their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
259
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 258 publications
(263 citation statements)
references
References 50 publications
0
259
0
4
Order By: Relevance
“…Despite recent progress in understanding the role of dry channels as important habitats for terrestrial arthropods (e.g. Wishart, 2000;Larned et al, 2007;Steward et al, 2011;Steward et al, 2012;Corti and Datry, 2015;Corti et al, 2013;Corti and Datry, 2014), the terrestrial phase is not yet integrated into bioassessment strategies. We also need to consider the entire hydrological cycle in order to allow a more comprehensive assessment of the ecological status of Mediterranean NPRS .…”
Section: Biological Research Challengesmentioning
confidence: 99%
“…Despite recent progress in understanding the role of dry channels as important habitats for terrestrial arthropods (e.g. Wishart, 2000;Larned et al, 2007;Steward et al, 2011;Steward et al, 2012;Corti and Datry, 2015;Corti et al, 2013;Corti and Datry, 2014), the terrestrial phase is not yet integrated into bioassessment strategies. We also need to consider the entire hydrological cycle in order to allow a more comprehensive assessment of the ecological status of Mediterranean NPRS .…”
Section: Biological Research Challengesmentioning
confidence: 99%
“…For example, in California, Mazor et al [118] demonstrated acceptable performance of current biomonitoring indices such as the Southern California Index of Biotic Integrity (IBI) for many intermittent streams. Moreover, innovative approaches, such as one based on terrestrial fauna [119,120] are being developed.…”
Section: Biomonitoring In Highly Variable Systemsmentioning
confidence: 99%
“…The alternatives therefore are entering dormancy until the conditions become again favorable, or being able to colonize the particular habitat from the outside. During the stream contraction process, pools are formed in the deeper parts of the stream, where lotic communities are gradually replaced by lentic others and even semiaquatic or terrestrially-derived biota (Stanley et al, 1997;Steward et al, 2012;Timoner et al, 2014a). In these pools, attached communities are progressively replaced by free-living (tychoplanktonic; Fazi et al, 2013) communities, and finally by subaerial communities when the drying is complete.…”
Section: Biofilms In Temporary Streamsmentioning
confidence: 99%